To be at Home house, work, and self in the modern world - Hentschke, Felicitas 1967-; Williams, James (De Gruyter Oldenbourg, 2018)
Houses and homes are dynamic spaces within which people work to organize and secure their lives, livelihoods and relationships. Written by a team of renowned historians and anthropologists, and and accompanied by original photography by Maurice Weiss, To Be at Home: House,Work, and Self in the Modern World compares the ways people in different societies and historical periods strive to make and keep houses and homes under conditions of change, upheaval, displacement, impoverishment and violence. These conditions speak to the challenges of life in our modern world. The contributors of this volume position the home as a new nodal point between work, the self and the world to explore people’s creativity, agency and labour. Houses and homes prove complex and powerful concepts – if also often elusive – invoking places, persons, objects, emotions, values, attachments and fantasies. This book demonstrates how the relations between houses, work and the self have transformed dramatically and unpredictably under conditions of capitalism and modernity – and continue to change today
Keywords: Wohnen; Internationaler Vergleich; Intersektionalität; Soziale Ungleichheit; Ausgrenzung; Nachbarschaft; Alltag; Aufsatzsammlung